Nominal Aggregate Size an Index to The Resilient Modulus Value of Hot Mix Asphalt - S. Neham, Sahar (International Journal of Engineering and Technology, 2018)
Properties and performance of hot mix asphalt are highly affected by aggregate as it is consists of 85 to 95 percent by weight and 75 to 85 percent by volume mineral aggregate. Resilient modulus was a very important parameter used either as input data in the procedure of pavement design or to evaluate the relative quality of materials. This research study the effect of nominal aggregate size on the resilient modulus value with different variationsÂ such as tested temperature, percent of asphalt cement and filler content, load duration, and asphalt viscosity. Results under different variables showed that nominal aggregate size has a significant effect on the resilient modulus value as well as resilient modulus value decreases by (21.04% - 26.66%) when the nominal aggregate size increases from 19mm to 25mm while it decreases by (22.43 - 29.50%) when the nominal aggregate size increases from 25mm to 37.3mm.Â